Chemoenzymatic Synthesis and Radical Scavenging of Sulfated Hydroxytyrosol, Tyrosol, and Acetylated Derivatives - Begines, Paloma; Biedermann, David; Valentová, Kateřina; Petrásková, Lucie; Pelantová, Helena; Maya, Inés; Fernández-Bolaños, José G; Křen, Vladimír (Journal of agricultural and food chemistry, 2019)
Potential metabolites of bioactive compounds are important for their biological activities and as authentic standards for metabolic studies. The phenolic compounds contained in olive oil are an important part of the human diet, and therefore their potential metabolites are of utmost interest. We developed a convenient, scalable, one-pot chemoenzymatic method using the arylsulfotransferase from Desulfitobacterium hafniense for the sulfation of the natural olive oil phenols tyrosol, hydroxytyrosol, and of their monoacetylated derivatives. Respective monosulfated (tentative) metabolites were fully structurally characterized using LC-MS, NMR, and HRMS. In addition, Folin-Ciocalteu reduction, 1,1-diphenyl-2-picrylhydrazyl radical scavenging, and antilipoperoxidant activity in rat liver microsomes damaged by tert-butylhydroperoxide were measured and compared to the parent compounds. As expected, the sulfation diminished the radical scavenging properties of the prepared compounds. These compounds will serve as authentic standards of phase II metabolites.
Keywords: Phenylethyl Alcohol; Free Radical Scavengers; Arylsulfotransferase; Acetylation; arylsulfotransferasa; hydroxytyrosol, tyrosol; bakteriální proteiny; fenoly; Phenols; Sulfates; vysokoúčinná kapalinová chromatografie; Bacterial Proteins; Molecular Structure; chemoenzymatic; sírany; metabolites; fenethylalkohol; olive phenols; Olive Oil; hmotnostní spektrometrie; biokatalýza; molekulární struktura; Chromatography, High Pressure Liquid; Desulfitobacterium; scavengery volných radikálů; Mass Spectrometry; arylsulfotransferase; Biocatalysis; olivový olej; acetylace